gga-miR-6634-5p Affects the proliferation and steroid hormone secretion of chicken (Gallus Gallus) granulosa cells by targeting MMP16 - Yixiang Tian; Xing Wu; Zihao Zhang; Yijie Li; Meng Hou; Ruirui Jiang; Donghua Li; Yanhua Zhang; Yulong Guo; Guoxi Li; Xiaojun Liu; Xiangtao Kang; et al. (Poultry Science)
MiRNAs are typically reported to play a negative regulatory role in post-transcriptional expression of target genes and are widely involved in a variety of biological processes such as growth, metabolism and reproduction. However, research on the role of miRNAs in the ovulation process of chicken ovaries is still insufficient compared to that in mammals. Here, we investigated the regulatory mechanisms of gga-miR-6634-5p in the growth and steroid hormone secretion of chicken granulosa cells (GCs) by targeting MMP16. We found that gga-miR-6634-5p significantly down-regulated the mRNA levels of proliferation-related genes (CCND1, CDK1, and CDK6), decreased cell viability, the number of EdU-labelled positive cells, and the percentage of S-phase cells, as analysed by quantitative real time PCR (qRT-PCR), cell counting kit-8 (CCK-8), 5-ethynyl-2′deoxyuridine (EdU) and flow cytometry analyses (P < 0.01 or P < 0.05). qRT-PCR and enzyme-linked immunosorbent assay (ELISA) results demonstrated that gga-miR-6634-5p up-regulated the expression of steroid synthesis-related genes (CYP19A1, 3β-HSD, StAR and FSHR) (P < 0.01 or P < 0.05), as well as the secretion of estradiol (E2) and progesterone (P4) (P < 0.01 or P < 0.05). Furthermore, we found that MMP16 protein and gene expression can be down-regulated by gga-miR-6634-5p and demonstrated that MMP16 is a target gene of gga-miR-6634-5p by dual luciferase reporter assay (P < 0.05). In addition, we found that MMP16 stimulated the proliferation of GCs, significantly inhibited the expression of steroid synthesis related genes (CYP19A1, StAR, 3β-HSD and FSHR), and decreased the secretion of E2 and P4 (P < 0.01 or P < 0.05), which was consistent with the inhibitory effect of gga-miR-6634-5p. It was further found by functional enrichment analysis, qRT-PCR, western blot (WB) and ELISA that MMP16 may play a regulatory role in GCs proliferation as well as steroid hormone secretion through the mTOR signaling pathway and PPAR signaling pathway. Therefore, this study demonstrates that gga-miR-6634-5p modulates the proliferation of chicken GCs and the secretion of steroid hormones by targeting MMP16, which may contribute to a better understanding of the functional mechanisms of miRNAs in the ovarian development of laying hens.